Entry Modes and Innovation: A Productivity Growth Perspective - Wollenberg, Alexander (2014)
This book discusses choices for hierarchical entry modes and ownership adjustments from a technology and knowledge transfer-linked productivity growth perspective using Japanese high-tech companies in China as examples. A quantitative analysis of panel data from the Toyo Keizai Kaigai Shinshutsu Kigyo Soran comprising data of 1881 Japanese companies’ subsidiaries from the high-tech industry in China which covers intervals of 17 years is linked with qualitative findings. The book introduces an econometric approach to business research by using the concept of residual productivity growth within a statistical application of panel data. A quantitative framework that measures the degree of efficiency in technology and knowledge transfer in the form of a residual productivity growth variable is developed and linked to ownership structures in subsidiaries over time. Quantitative findings are then analyzed in a qualitative part using case studies. The book combines methods used in business research with macro- and micro-economic analysis.